Flood disaster risk identification using integrated fuzzy MCDA and GIS in Song Hinh District, Phu Yen Province - Tong, Hanh T.; Pham, Mai Phuong; Nguyen, Nga T.T. (Journal of Degraded and Mining Lands Management, 2026)
This study presents an integrated approach for flood risk zonation using Geographic Information Systems (GIS), which combines spatial multi-criteria analysis (MCDA) with the Group Fuzzy Analytic Hierarchy Process (GFAHP) and fuzzy overlay techniques. Nine flood-influencing factors were considered, namely Digital Elevation Model (DEM), Slope, Normalized Difference Vegetation Index (NDVI), Horizontal Overland Flow Distance (HOFD), Vertical Overland Flow Distance (VOFD), Topographic Position Index (TPI), Topographic Wetness Index (TWI), Curve Number (CN), and Modified Fournier Index (MFI). Each factor was classified into five categories and weighted based on expert judgment through GFAHP, which effectively addresses uncertainty and variability in expert evaluations. The weighting values demonstrated that the DEM (0.248) and slope (0.188) exert the greatest influence on flood hazard. Results showed that 27% of the area belongs to the high and very high-risk zones, primarily concentrated along the Hinh and Ba rivers and around hydropower reservoirs. The derived weights were integrated in the GIS environment using fuzzy overlay to produce a flood risk map with five susceptibility levels, ranging from very low to very high. The findings highlight the effectiveness of the proposed approach as a decision-support tool for spatial planning, resource management and disaster risk reduction and demonstrate its potential applicability to other regions with comparable data conditions.